Clinical Presentations of Melanoma in African Americans, Hispanics, and Asians. Issue 6 (June 2019) - Higgins, Shauna; Nazemi, Azadeh; Feinstein, Shera; Chow, Maggie; Wysong, Ashley
Abstract : BACKGROUND: Skin cancer has traditionally been studied in Caucasian skin. Although it does occur with increased relative frequency in Caucasians, patients with skin of color suffer from elevated morbidity and mortality when diagnosed with skin cancer. OBJECTIVE: To detail the unique demographic, clinical, and genetic features of melanoma in patients with skin of color, including Hispanic, African American, and Asian patients. MATERIALS AND METHODS: A PubMed search was conducted spanning dates 1947 to June 2017. A total of 246 articles were screened, from which 69 were included in this review. RESULTS: Relative to Caucasians, melanoma has unique demographic, clinical, and genetic features in African Americans, Hispanics, and Asians that include gender and subtype predominance. CONCLUSION: Familiarization with these unique presentations of skin cancer in skin of color is imperative to accurate identification and treatment of cutaneous malignancies in these populations and ultimately to improved disease-related outcomes.